Non-structural Proteins of Severe Fever With Thrombocytopenia Syndrome Virus Suppress RNA Synthesis in a Transcriptionally Active cDNA-Derived Viral RNA Synthesis System - Ren, Fuli; Shen, Shu; Ning, Yun-Jia; Wang, Qiongya; Dai, Shiyu; Shi, Junming; Zhou, Min; Wang, Hualin; Huang, Chaolin; Zhang, Ding-Yu; Deng, Fei (Frontiers in Microbiology, 2021)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by the tick-borne SFTS bunyavirus (SFTSV) resulting in a high fatality rate up to 30%. SFTSV is a negative-strand RNA virus containing three single-stranded RNA genome segments designated as L, M, and S, which respectively encode the RNA-dependent RNA polymerase (RdRp), glycoproteins Gn and Gc, nucleoprotein (N) and non-structural protein (NSs). NSs can form inclusion bodies (IB) in infected and transfected cells. Previous study has provided a clue that SFTSV NSs may be involved in virus-like or viral RNA synthesis; however, the details remain unclear. Our work described here reveal that SFTSV NSs can down-regulate virus-like RNA synthesis in a dose-dependent manner within a cDNA-derived viral RNA synthesis system, i.e., minigenome (−) and minigenome (+) systems based on transfection, superinfection, and luciferase reporter activity determination; meanwhile, NSs also shows weak inhibitory effect on virus replication. By using Co-immunoprecipitation (Co-IP) and RT-PCR combining with site directed mutagenesis, we found that NSs suppresses virus-like RNA or virus replication through interacting with N but not with RdRp, and the negative regulatory effect correlates closely with the IB structure it formed but is not associated with its role of antagonizing host innate immune responses. When the cytoplasmic structure of IB formed by SFTSV NSs was deprived, the inhibitory effect of NSs on virus-like RNA synthesis would weaken even disappear. Similarly, we also evaluated other bandavirus NSs that cannot form IB in neither infected nor transfected cells, and the results showed that the NSs of Heartland bandavirus (HRTV) didn’t show significant inhibitory effect on virus-like RNA synthesis within a minigenome system. Our findings provide experimental evidence that SFTSV NSs participate in regulating virus-like or viral RNA synthesis and the negative effect may be due to the NSs - N interaction.